Die deutschen Ortsnamen und Mundarten in kulturgeographischer und kulturlandschaftsgeschichtlicher Beleuchtung: Zu zwei neueren Werken von Adolf Bach - Overbeck, Hermann (ERDKUNDE, 1957)
The announcement of publication of two philological reference books by the Rhenish philologist and folklorist Adolf Bach is taken as an occasion to point out the important role played by place name and dialect studies in recent developments in the field of human geography. Bach's principal ideas about the problems of German place name studies as regards areal distribution as well as chronological sequence deserve the geographer's attention mainly for the source value which place names have in the interpretation of the German cultural landscape, although this source value is not undisputed in certain instances. In an interpretation of the distribution of place name types, not only processes of settlement but culture movements must also be taken into account. Although the first method of interpretation has found general acceptance in geography, mainly by the way of landscape history studies, the results of culture area studies have so far been little used for the geographical applications of place name research; this is despite the fact that from the latter there are connexions through the social groups of communication with the functional areal units of cultural landscape research. These links with culture area studies and regional history may also be noted as regards the problem of the importance for geography of language communities and especially dialect areas. Once again it is the social groups of communication within which the cultural processes of mixture and assimilation take place which are of paramount importance for the formation of dialects. Behind these social groups of communication, however, are the human habitats, to which at present increased attention is given in both functional human geography as well as regional geography. In dialect research the areas of political organization of the late Middle Ages and the early Modern Period play a decisive role; they are, incidentally, of particular importance for a historical geography in the sense of a study of the history of the cultural landscape. Of even greater importance in geography are, however, those influences on dialects which are effected through the areas of economic organization, especially the recent economic regions. Thus dialect research as a neighbouring subject can supply some help, so far little used, for the geographical study of the cultural landscape.